Heterogeneous Nuclear Ribonucleoprotein A1 Loads Batched Tumor-Promoting MicroRNAs Into Small Extracellular Vesicles With the Assist of Caveolin-1 in A549 Cells - Li, Yangyang; Zhang, Jian; Li, Sha; Guo, Chongye; Li, Qian; Zhang, Xin; Li, Meng; Mi, Shuangli (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs in small extracellular vesicle (sEV-miRNAs) have been widely investigated as crucial regulated molecules secreted by tumor cells to communicate with surroundings. It is of great significance to explore the loading mechanism of sEV-miRNAs by tumor cells. Here we comprehensively illustrated a reasoned loading pathway of batched tumor-promoting sEV-miRNAs in non-small cell lung cancer (NSCLC) cell line A549 with the application of a multi-omics method. The protein heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) was strictly selected as a powerful sEV-miRNAs loading protein from miRNA-binding proteome and further verified through small RNA sequencing after hnRNPA1 silence. In terms of the mechanism, SUMOylated hnRNPA1 in sEV was verified to control sEV-miRNAs loading. Subsequently, as a scaffolding component of caveolae, caveolin-1 (CAV1) was detailedly demonstrated to assist the loading of SUMOylated hnRNPA1 and its binding miRNAs into sEV. Inhibition of CAV1 significantly prevented SUMOylated hnRNPA1 from encapsulating into sEV, resulting in less enrichment of sEV-miRNAs it loaded. Finally, we confirmed hnRNPA1-loaded sEV-miRNAs could facilitate tumor proliferation and migration based on database analysis and cytological experiments. Our findings reveal a loading mechanism of batched tumor-promoting sEV-miRNAs, which may contribute to the selection of therapeutic targets for lung cancer.